Richard Minne zestig : een vriendenboek samengesteld ter gelegenheid van zijn zestigste verjaardag, 1891-1951 - Mussche, Achilles; Cantré, Jozef; Teirlinck, Herman; Huysmans, Camille ([Gent] : Leesclub Boekuil, 1951)
Bibliotheek Camille Huysmans
Nederlands
Monografie
Keywords: Minne, Richard